ANALISIS PENGARUH INSENTIF TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI (Studi Pada Karyawan Perusahaan Air Minum Kabupaten Jepara) - Mera Diviani, Gracetiara; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2015)
Incentives as a means of motivation that encourages employees to work with optimal performance, which is intended as an extra income outside of salaries or wages that have been determined. This study entitled